Gingipain injection affects intestinal oxidantantioxidant status and alkaline phosphatase in overfed zebrafish - ALTURFAN, EBRU IŞIK (My University, 2023)
Objective: Porphyromonas gingivalis (P. gingivalis), a major periodontopathogen, is associated with overfeeding disorders, including metabolic syndrome. Gingipains are one of the most powerful endotoxins of P. gingivalis. Our aim was to reveal the effects of gingipain injections on the intestinal oxidant-antioxidant status and alkaline phosphatase (ALP) activity in overfed zebrafish. Materials and Methods: Four groups of healthy adult zebrafish were placed in random tanks as C: Control (n=15); GP: Gingipain (n=15); OF: Overfeeding (n=15); and OF+GP: Overfeeding+Gingipain (n=15) groups. At the end of the experiment, levels of intestinal lipid peroxidation (LPO) and ALP, glutathione S-transferase (GST), and catalase (CAT) activities were evaluated. Results: Intestinal LPO was significantly lower in the GP and OF groups compared to C. Gingipain injection in OF (OF+GP) significantly elevated LPO when compared to C, GP, and OF groups. ALP activities decreased significantly in the GP, OF, and OF+GP compared to C. GST activities increased significantly in the GP when compared to C. Decreased GST activities were observed in the OF and OF+GP. This decrease was less in OF+GP. CAT activities significantly decreased in all groups when compared to C. Conclusion: Our findings demonstrate that gingipain injection alters the ALP activity and intestinal oxidant-antioxidant status in overfed zebrafish.
Keywords: Diş Hekimliği; Yaşam Bilimleri; Biyokimya; Sağlık Bilimleri; Temel Bilimler; Dentistry; Life Sciences; Biochemistry; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Klinik Tıp; Doğa Bilimleri Genel; Biyoloji ve Biyokimya; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; ÇOK DİSİPLİNLİ BİLİMLER; BİYOKİMYASAL ARAŞTIRMA YÖNTEMLERİ; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); CLINICAL MEDICINE; NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; DENTISTRY, ORAL SURGERY & MEDICINE; MULTIDISCIPLINARY SCIENCES; BIOCHEMICAL RESEARCH METHODS; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Multidisipliner; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Multidisciplinary; Gingipain; zebrafish; oxidative stress